Management Issues within Entrepreneurship Education in Secondary Schools in Poland - Tomasz RACHWAL (Communications of International Proceedings, 2021)
Entrepreneurship in the European education system is treated as one of the eight key competences, as a result of which it is commonly taught to pupils and students in EU Member States. It also occupies a special place in the education system in Poland, where this competence is shaped already from primary school and even kindergarten. This education has a special place in secondary schools, where, since 2002, the subject of basics of entrepreneurship has been implemented, which is compulsory for all students. One of the objectives of this subject is to prepare students for participation in socio-economic life, including professional activity and conducting business. Therefore, an important element of entrepreneurship education at secondary school level is the formation of knowledge-based management skills in students. In the light of these premises, the objective of this article is to present the results of the analysis of the core curriculum provisions in Poland in the field of entrepreneurship education in terms of objectives and content related to management. To this end, a comparison was made between the provisions of the old (2012) and the new core curriculum (2018), in force from school year 2019/2020. The results of the analysis indicate the growing importance of management objectives and contents in entrepreneurship education in Poland as a result of the curriculum reform of the education system. This should contribute to better preparing students for managerial functions and running their own business. The article ends with conclusions and recommendations for educational practice.
Keywords: Entrepreneurship Education; Entrepreneurial Competence; Managerial Skills; Management in Education